Influence of achieved paternity on quality of life in testicular cancer survivors. (29th October 2012) - Stoehr, Brigitte; Schachtner, Lydia; Pichler, Renate; Holzner, Bernhard; Giesinger, Johannes; Oberguggenberger, Anne; Leonhartsberger, Nicolai; Horninger, Wolfgang; Steiner, Hannes
Abstract : What's known on the subject? and What does the study add? It is known that testicular cancer, as with any malignancy, influences many different aspects of quality of life and that surgical treatment and chemotherapy negatively influence male fertility. The study shows the importance of achieved paternity in those testicular cancer survivors with a declared wish to father a child. The study used a QoL questionnaire EORTC QLQ‐TC 26 to supplement the existing QoL questionnaire QLQ‐C30 of the European Organisation for the Research and Treatment of Cancer in patients with cancer. OBJECTIVE:   To investigate the influence of achieved/non‐achieved paternity on quality of life (QoL) in testicular cancer (TC) survivors. PATIENTS AND METHODS:   We invited TC survivors treated at our department between 1989 and 2006 to complete a QoL assessment, including the European Organisation for the Research and Treatment of Cancer QoL questionnaire, EORTC QLQ‐C30 (version 3.0©)/+ TC26, and follow‐up questions.   A total of 311 TC survivors answered the questionnaire, of whom 207 patients who did not desire paternity were excluded. The remaining 104 patients who stated a desire for paternity after TC treatment were further divided in group A (TC survivors who achieved paternity; n = 51) and group B (TC survivors who did not achieve paternity; n = 53).   The data obtained were statistically analysed. RESULTS:   Significant differences between groups regarding QoL were detected for social functioning ( P = 0.002), emotional functioning ( P = 0.001), general QoL ( P = 0.018), fatigue ( P = 0.025), pain ( P = 0.01), sleeping problems ( P = 0.024), treatment satisfaction ( P = 0.039), financial aspects ( P = 0.006), sexual problems ( P = 0.017), body image problems ( P < 0.001), dyspnoea ( P = 0.005) and cognitive functioning ( P = 0.019).   For all scales except 'sexual enjoyment', patients in group A were found to have a better long‐term QoL than those in group B. CONCLUSIONS:   Whilst acknowledging the shortcomings in retrospective analyses, we believe our data clearly underline the important impact on QoL for TC survivors of achieved paternity.   Counselling patients early at diagnosis as well as using cryopreservation of semen in all potential patients before treatment (only excluding patients definitely claiming they do not wish to achieve paternity) should therefore be regarded as the standard of care.